Vibration control by active integrated control system under bidirectional ground motions. Issue 3 (February 2021) - Akyürek, Osman; Suksawang, Nakin
To improve the safety and security of the structures with irregular plan configuration, the new torsionally effective passive control system (ICS) was first proposed by the author, which utilizes a new design configuration to dissipate the unwanted energy from the structures in the lateral and torsional directions. In this research, a new active structural control approach, which is the active form of the ICS (or active integrated control system, AICS), is introduced as an alternative active control system, especially for the buildings with torsional sensitivity. In the design of active system configurations, two actuators driven by the linear quadratic regulator (LQR) are implemented and used to apply the optimum control forces to the ATMDs and AICS. For examining the performance of the proposed system configuration, the ﬁnal design is applied to the 9-story Benchmark steel structure subjected to bidirectional three historical earthquakes. The obtained results show the overall performance of structural performance by using the AICS is substantially improved as compared to conventional ones (ATMDs) under selected ground accelerations with a 3% to 6% improvement in the lateral directions and by nearly 20% in the torsional direction in terms of the peak and root mean square response reduction.